Implementation of Sensory Marketing Strategy in Increasing Consumer Perception of Quality and Purchase Interest in Wilna Family MSME Products - Khafidzoh; Herliani, Dini; Nurasyiah, Fitri; Nasrullah, Muhamad; Sopian, Yepi (Formosa Journal of Sustainable Research, 2024)
This study aims to analyze the application of sensory marketing strategies in enhancing consumer perceptions of quality and purchase intention towards MSME Wilna Family products. Sensory marketing is a marketing approach that utilizes the human senses to create positive and memorable experiences for consumers. This research uses a quantitative method by distributing questionnaires to 100 respondents who are consumers of Wilna Family products. Data analysis was performed using linear regression to assess the influence of each sensory marketing element (sight, hearing, smell, touch, and taste) on consumer perceptions of quality and purchase intention. The results show that sensory marketing elements significantly affect consumer perceptions of quality and purchase intention. Among the five elements studied, sight and taste have the greatest influence. These findings have important implications for MSME Wilna Family in designing more effective marketing strategies by leveraging sensory marketing to enhance competitiveness and consumer loyalty